1987
DOI: 10.2131/jts.12.111
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous tumors in F344/DuCrj rats from 12 control groups of chronic and oncogenicity studies.

Abstract: The types and incidences of spontaneous tumors in F344/DuCrj rats were examined in 960 males and 959 females served as the control groups of separate twelve 2-year chronic and oncogenicity studies carried out during a 1978-1983 period. The major tumors occurred at more than 5% incidence were leukemia (mononuclear cell), testicular interstitial cell tumor, preputial gland adenoma, pituitary anterior adenoma, thyroid C-cell adenoma, adrenal pheochromocytoma and subcutis fibroma for males, and leukemia, uterine e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…The morphological features of the F344 rat MM are similar to those of human or asbestos-induced murine MM, but they are more uniform and, typically, show a simple papillary growth of epithelial-type cells [10,23,24,31]. Previously, we established cell lines from rat spontaneous mesothelioma [18].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The morphological features of the F344 rat MM are similar to those of human or asbestos-induced murine MM, but they are more uniform and, typically, show a simple papillary growth of epithelial-type cells [10,23,24,31]. Previously, we established cell lines from rat spontaneous mesothelioma [18].…”
Section: Introductionmentioning
confidence: 94%
“…In Fisher 344 (F344) rats, abdominal MM is a rather rare spontaneous tumor with an aged male predominance [11,12,23,24]. The morphological features of the F344 rat MM are similar to those of human or asbestos-induced murine MM, but they are more uniform and, typically, show a simple papillary growth of epithelial-type cells [10,23,24,31].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that C-cell tumor developed with a high incidence in Wistar and F344 rats but that it developed with a low incidence in SD rats 8 . Meanwhile, the incidence of C-cell tumor in female Harlan SD rats (25.43%) in the National Toxicology Program (NTP) 9 was far higher than that in the historical control data in female Charles River SD rats (7.21%) 10 and the above data from F344 rats 4 , 5 , 6 , 7 . Therefore, it seems that there are differences in tumor incidence between the substrains of suppliers.…”
Section: Resultsmentioning
confidence: 81%
“…In the historical control data that were published between 1987 and 2011, the incidences of C-cell adenoma in the thyroid of F344 rats were 9.2 to 15.42% in males and 6.7 to 12.14% in females 4 , 5 , 6 , 7 . The incidence in 2005–2009 in the present survey was higher than those data.…”
Section: Resultsmentioning
confidence: 99%
“…Although most of the spontaneous pituitary tumors in rats are thought to be benign, malignant tumors are recognized with a low incidence (6,7,10,15,17,18,20). In rats, there is a dearth of information dealing with xenobiotic-induced pituitary carcinomas, including estrogen-induced tumors.…”
Section: Introductionmentioning
confidence: 99%